Adenoid cystic carcinoma of the palate and tongue: Report of two cases - Sumanta Kumar Kolay; Raman Kant Sinha; Narendra Nath Singh; Rajkumar Parwani (Wolters Kluwer Medknow Publications, 2014)
Adenoid cystic carcinoma is a rare cancer that arises in major and minor salivary glands with an affinity for nerve invasion. The most common malignancies associated with head and neck and perineural spread are tumors of the minor salivary glands, mucosal and cutaneous origin. However, it is the commonest malignant tumor salivary glands, the palate being the commonest site. A 45-years old female patient reported with an asymptomatic growth over left lateral border of the tongue; since last three months. Computed tomography scan revealed the nature of the growth was malignant. An incisional biopsy was performed. Another 45-years old female patient reported with complaints of pain and swelling over palate since last one month. Clinical examination revealed a large multi-lobulated growth over left side of palate. Provisional diagnosis as a salivary gland neoplasm was given. An incisional biopsy was performed. Histological examination confirmed the diagnosis as adenoid cystic carcinoma of tongue as well as of palate for case one and two respectively and both the case were referred to surgical excision of tumors and advised for periodic follow up. Adenoid cystic carcinoma is a slowly growing but highly invasive cancer with high recurrence rate. Lymphatic spread to local lymph nodes is rare. Pleomorphic adenoma with cribriform pattern and polymorphous low grade adenocarcinoma should be considered in the differential diagnosis since they present similarities in the histological pattern. Surgery is the cornerstone of treatment, and its extension depends primarily on the size of the tumor.